Minimal change prion retinopathy: Morphometric comparison of retinal and brain prion deposits in Creutzfeldt-Jakob disease. (September 2022) - Goodwill, Vanessa S.; Dryden, Ian; Choi, Jihee; De Lillo, Chiara; Soldau, Katrin; Llibre-Guerra, Jorge; Sanchez, Henry; Sigurdson, Christina J.; Lin, Jonathan H.
Abstract: Sporadic Creutzfeldt-Jakob disease (sCJD) is the most commonly diagnosed human prion disease caused by the abnormal misfolding of the 'cellular' prion protein (PrP C ) into the transmissible 'scrapie-type' prion form (PrP Sc ). Neuropathologic evaluation of brains with sCJD reveals abnormal PrP Sc deposits primarily in grey matter structures, often associated with micro-vacuolar spongiform changes in neuropil, neuronal loss, and gliosis. Abnormal PrP Sc deposits have also been reported in the retina of patients with sCJD, but few studies have characterized the morphology of these retinal PrP Sc deposits or evaluated for any retinal neurodegenerative changes. We performed histopathologic and morphometric analyses of retinal and brain prion deposits in 14 patients with sCJD. Interestingly, we discovered that the morphology of retinal PrP Sc deposits generally differs from that of brain PrP Sc deposits in terms of size and shape. We found that retinal PrP Sc deposits consistently localize to the outer plexiform layer of the retina. Additionally, we observed that the retinal PrP Sc deposits are not associated with the spongiform change, neuronal loss, and gliosis often seen in the brain. The stereotypic morphology and location of PrP Sc deposits in sCJD retinas may help guide the use of ocular imaging devices in the detection of these deposits for a clinical diagnosis.